Evaluating the occurrence of cryptic invasions of a rocky shore barnacle, Semibalanus cariosus, between the north-eastern Pacific and Japan. Issue 2 (7th February 2018) - Yorisue, Takefumi; Yoshioka, Yuki; Sakuma, Kay; Iguchi, Akira
Abstract: Many coastal barnacles are introduced to non-native regions. However, data are lacking on cryptic invasion, which is defined as an invasion that remains unrecognised because the invader is mistaken for a native or previously introduced species or clade. In this work, cryptic invasions of an intertidal barnacle, Semibalanus cariosus, between Japan and the north-eastern Pacific were evaluated based on population genetic analyses. A significant genetic differentiation was found between the Japanese and north-eastern Pacific populations, suggesting a limited introduction of non-native genotypes between these regions. Haplotype frequencies did not differ significantly between the past (museum samples collected in 1971 from Hokkaido, Japan) and present Japanese populations, implying the rare occurrence of human-mediated migration from the north-eastern Pacific to Japan. Migrate-n analysis revealed a low level of directional gene flow in S. cariosus from the north-eastern Pacific to Japan, possibly by natural stepping-stone dispersal via directional water currents or human-mediated transport.